Epidemiology of Listerosis in Animal and Human in Ethiopia - Sagni Diba Bayata (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
Listeriosis is an important food borne bacterial disease for both human and animals. The objective of the paper was to review the Epidemiology of listeria in animal and human in Ethiopia. From the studies conducted in different area of the country 7 species of Listeria were reported namely: L. monocytogenes, L. innocua, L. welshimeri, L. seeligeri, and L. ivanovii, and L. grayi, L. welshimeri. Among those species L. monocytogenes is the most species that is zonootic for both humans and animals. Occasionally L. seeligeri, L. ivanovii are affected animals and humans. The overall prevalence of the listeriosis was reported in the country: 3.8%, 14%, 20%, 20.8%, 24.2%, 25, 26.1, 26.6%, 27.5%, 28.4%, 32.6%, 32.9% and 42.9% respectively. The most common source of infection: human feces, animal feces, aborted fetus, soil, both farm and surface water troughs, animals feed and the walls. The main Reservoir, risk factors for distribution of the disease are forage, water, mud, silage and host, management, pathogenic risk factors respectively. Pregnant women and their fetuses, newborn babies, the elderly and immunocompromised individuals are the people at risk for the disease. The major clinical forms of listeria in cattle are encephalitis, abortion, endocarditics, conjunctivitis, metrits and meningitis. The ways to control of disease in foods relies largely on Hazard analysis critical point approach and the establishment of effective critical control points in food industry. The preparation of silage should be made for good quality, with early cutting of grass, reduce contamination with soil and ensuring optimal anaerobic fermentation, which will insure that the pH falls below 5 levels for inhibited growth of Listeria species. They must be improving hygienic management for animals and health educations for peoples about the disease for reduce infection.